2015
DOI: 10.1039/c5ra19835f
|View full text |Cite
|
Sign up to set email alerts
|

BiOI solar cells

Abstract: An inorganic solar cell was constructed using a thin compact supporting layer of titania with BiOI nanoflakes as a functional material, a Pt/FTO cathode and a I3−/I− redox electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 17 publications
2
36
1
Order By: Relevance
“…The integrated J SC values of the EQE spectra closely matched the J SC values measured through current density-voltage (J-V) sweeps ( Table 1). An EQE of 80% exceeds the highest previously reported for BiOI [18] and is higher than recently reported EQEs from other bismuth halides and chalcohalides (discussed in the Introduction). [10,14,42] We found that we could further improve efficiency by lowering the deposition temperature of ZnO from 100 to 80 °C.…”
contrasting
confidence: 61%
See 3 more Smart Citations
“…The integrated J SC values of the EQE spectra closely matched the J SC values measured through current density-voltage (J-V) sweeps ( Table 1). An EQE of 80% exceeds the highest previously reported for BiOI [18] and is higher than recently reported EQEs from other bismuth halides and chalcohalides (discussed in the Introduction). [10,14,42] We found that we could further improve efficiency by lowering the deposition temperature of ZnO from 100 to 80 °C.…”
contrasting
confidence: 61%
“…These J SC values are almost double the highest previously reported for BiOI. [18] An important reason for the high performance of our devices is the densely packed morphology of the NiO x ( Figure S12, Supporting Information) and BiOI layers (Figure 3a,b), as well as our conformal AP-CVD ZnO layer (Figure 3a-c). These led to low leakage, as can be seen from the low reverse-bias dark current density of our optimized device (Figure 4a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…17 Many of these PIMs have recently been explored for photovoltaic applications. These include BiI 3 , 19,20 (CH 3 NH 3 ) 3 Bi 2 I 9 , [21][22][23][24] BiSI, 25,26 BiSeI, 25,26 K 3 Bi 2 I 9 , 27 Rb 3 Bi 2 I 9 , 27 Cs 3 Bi 2 I 9 , 27 BiOI, 28,29 Cs 3 Sb 2 I 9 , 30 SbSI, 31 SbSeI, 31 Sb 2 Se 3 , 32 CuSbSe 2 , 33,34 (CH 3 NH 3 ) 2 KBiCl 6 , 35 and SnS. 36 Many other recent works have been written on understanding the properties of hybrid lead-halide perovskites that make them excellent solar absorbers, e.g., energetic carrier screening via polarons, which may lead to new design rules.…”
Section: Introductionmentioning
confidence: 99%